Continuous Professional Development Strategy in Improving the Competence of Arabic Language Teachers in Islamic Boarding School - Sidqi, Muhammad Hudhel; Taufiqurrochman, Raden; Ifawati, Nur Ila (Nurul Jadid University, 2025)
The professional development of Arabic language teachers is a strategic priority in Islamic educational institutions to ensure instructional quality and pedagogical relevance. This study investigates the implementation of Continuous Professional Development (CPD) strategies in enhancing teacher competence at Al-Mashduqiah Islamic Boarding School, Probolinggo. Employing a descriptive qualitative method, data were collected through interviews with caregivers and teachers, classroom observations, and analysis of institutional documents. The findings reveal that Arabic language teachers at the pesantren demonstrate four core competencies pedagogical, professional, personal, and social as mandated by national education standards. CPD at Al-Mashduqiah is systematically implemented through self-development programs, scientific publications, and innovative instructional practices. Supporting factors include a conducive Arabic-speaking environment, regular training sessions, and the integration of Arabic in daily communication. However, challenges such as high teacher workload, limited technological integration, and external teaching assignments persist. This study concludes that the CPD model at Al-Mashduqiah offers a viable and sustainable framework for enhancing Arabic language teacher competence and serves as a reference for similar Islamic educational settings aiming to strengthen professional teaching capacity.